Business Strategy in Islamic Boarding School: A Case Study of Pesantren Hidayatullah Depok Indonesia - Ramadini, Kintan Nur; Hasanah, Neneng; Irfany, Mohammad Iqbal (Penerbit Goodwood, 2023)
Purpose: Abstract. This study aims to identify the strengths, weaknesses, opportunities, threats, and strategic priorities in the development of a business unit in a pesantren, a culturally rooted Islamic boarding school in Indonesia. Methodology: Employing ANP-SWOT analysis, this study indicates that strengths and opportunities are the main priorities in developing pesantren’s business unit. The most influential aspects of strengths, weaknesses, opportunities, and threats are cooperation with internal and external parties in developing business and marketing management that is not optimal Results: Islamic boarding schools can play a more important role in economic activities as producers that meet community needs, in particular, and even supply a broader market. The most important strategy is to improve the quality of human resources by improving the mindsets and skillsets of business activities.